FEM analysis in the hip joint reconstructed with classical and modified hip resurfacing - Anna Maria RYNIEWICZ; Tomasz MADEJ (Engineering Transactions, 2017)
The aim of the work is personalized strength analysis using finite element method (FEM), carried out in the virtual hip joint supported by the hip resurfacing. The material for the procedure was the clinical case of patient, recommended to the resurfacing operation. The preoperative strength analysis was carried out on a numerical model of the patient's hip belt, reconstructed on the basis of computed tomography. The research material were implanted prostheses: BIRMINGHAM Hip Resurfacing System (BHR) and Birmingham Mid Head Resection (BMHR). The strength analysis was carried out using Femap NE / Nastran v.8.3. Huber-Mises-Hencky (HMH) hypothesis was assumed to determine and evaluation of stress and displacements in the structure of the prosthesis and periarticular tissues. The distributions of the stresses in the prosthesis and the surrounding tissues after resurfacing operation have not too large values. In the case under consideration, they do not exceed the physiological resistance of tissues and can stimulate bone formation processes.